Troubled Bodies : Critical Perspectives on Postmodernism, Medical Ethics, and the Body - Komesaroff, Paul A. (Book collections on Project MUSE., 1995)
Setting out the implications of the postmodern condition for medical ethics, Troubled Bodies challenges the contemporary paradigms of medical ethics and reconceptualizes the nature of the field. Drawing on recent developments in philosophy, philosophy of science, and feminist theory, this volume seeks to expand familiar ethical reflections on medicine to incorporate new ways of thinking about the body and the dilemmas raised by recent developments in medical techniques. These essays examine the ways in which the consideration of ethical questions is shaped by the structures of knowledge and communication at work in clinical practice, by current assumptions regarding the concept of the body, and by the social and political implications of both. Representing various perspectives including medicine, nursing, philosophy, and sociology, these essays look anew at issues of abortion, reproductive technologies, the doctor-patient relationship, the social construction of illness, the cultural assumptions and consequences of medicine, and the theoretical presuppositions underlying modern psychiatry. Diverging from the tenets of mainstream bioethics, Troubled Bodies suggests that, rather than searching for the correct "coherent perspective" from which to draw ethical principles, we must apprehend the complexity and diversity of the discursive systems within which we dwell.